Do we live in a Marxian world? - Franco, J. Agustín (Technological and Economic Development of Economy, 2018)
This paper proposes a scientific discussion from a Marxian-feminist point of view as a critical response to the European “austerity policies”. Nowadays global inequalities are very relevant, particularly a proletarization process based on an increase in class struggle, growing inequalities, unsustainability and the transnational concentration of power and wealth. The neoliberal approach ignores Marx’s theory and suggests that the Marxian view fails to explain the current economic system. However, I believe this to be a (dishonest) simplification of Marx’s theory (because data is very clear). This misrepresentation has a negative effect on the overall validity and sustainability of several European policies, mainly distribution and migration policies. Consequently, some policy recommendations need to be readdressed, including from a feminist point of view.First published online 30 January 2017